Model Three Lines of Defense dalam Sistem Pengendalian Risiko Organisasi Pendidikan - Intan Nurainia; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
The Three Lines of Defense Model serves as a structured framework in educational organizations to strengthen risk management and governance systems. This study explores the conceptual implementation of the model within educational institutions through a literature-based approach. Data were obtained from relevant academic sources and analyzed through three stages: identification of core issues in risk control, classification of concepts based on the three defense lines, and synthesis to formulate a conceptual framework. The analysis reveals that the first line, represented by operational units, plays a crucial role in direct risk control; the second line ensures compliance and supervises system adequacy; and the third line, internal audit, provides independent assurance on the effectiveness of governance. Integrating these three layers strengthens accountability, transparency, and institutional resilience. The Three Lines of Defense Model offers a practical approach for developing sustainable and transparent risk management systems in educational organizations.